ANIMALS IN ADVERTISING (LITERATURE REVIEW) - Yuliya V. Massalskaya; Anastasiya V. Nikolaeva (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. The article is a review of material on the topic of the reasons for using animals in various kinds of advertising. The animal species are examined in the light of the emotions, stereotypes and symbols they carry with them.